Evaluation of antioxidant, anti-inflammatory, anticancer activities and molecular docking of Moringa oleifera seed oil extract against experimental model of Ehrlich ascites carcinoma in Swiss female albino mice - Aldayel, Tahany Saleh; Gad El Hak, Heba N.; Nafie, Mohamed S.; Saad, Raneem; Abdelrazek, Heba M. A.; Kilany, Omnia E. (BMC complementary and alternative medicine, 2023)
The current research intended to evaluate the antitumor properties of Moringa oleifera oil extract (MOE). Fifty-six female Swiss albino mice were employed in this study. Animals were assigned into four groups: control (C) group, moringa oil extract (MOE) group administered (500 mg/kg b. wt) MOE daily via gavage, Ehrlich ascites carcinoma (EAC) group and EAC group administered daily with (500 mg/kg b.wt) MOE for two weeks (EAC/MOE). The results showed that MOE significantly ameliorated the EAC increase in body weight and reduced the EAC cell viability. In addition, they upgraded the levels of hepatic and renal functions, inflammatory cytokines, oxidative stress markers and EAC-induced hepatic and renal histopathological changes. Treatment of EAC with MOE induced antitumor, anti-inflammatory and antioxidant effects and normalized most of the tested parameters besides the histopathological alterations in both renal and hepatic tissues. HPLC for the MOE identified Cinnamic acid, Ellagic acid, Quercetin, Gallic acid, Vanillin and Hesperidin as major compounds. The molecular docking study highlighted the virtual binding of the identified compounds inside the GSH and SOD proteins, especially for Quercetin which exhibited promising binding affinity with good interactive binding mode with the key amino acids. These results demonstrate that the antitumor constituents of MOE against EAC induced oxidative stress and inflammation by preventing oxidative damage and controlling EAC increase.